Riesgo psicosocial del paciente con diabetes mellitus tipo II y complicación de la insuficiencia renal crónica - Hospital de Apoyo II de Sullana - Hinostroza Flores, Gissela (2019)
This research correlative type, was conducted in patients with diabetes mellitus type II in order to determine the relationship between psychosocial risk and complication of chronic renal failure in patients with diabetes mellitus type II Hospital Support II-2, Sullana. The sample universe consisted of 60 patients with type II diabetes mellitus; The instruments used were: Test Psychosocial Risk level: self-social support in patients with type II diabetes mellitus consisting of three parts I. general data suffers or IRC II III test self-esteem social support. The results were processed in SPSS version 23 and in single and double tables. For the statistical analysis, the Chi square test of independence of criteria was used, with a level of significance of 5 percent. It was found that 75% of patients show Psychosocial Risk and 68% have CRF; the statistical test of independence criterion chi- square shows that there is significant relation between the level of psychosocial risk and complication of chronic renal failure in patients with diabetes mellitus type II. (P <0.05).